FINANCIAL LITERACY FOR EARLY CHILDHOOD: PARENTAL FINANCIAL PERCEPTION AND SOCIALIZATION - Umi Julaihah; Nurlaeli Fitriah; Yhadi Firdiansyah (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2023)
Financial literacy becomes one of basic life skills that should be instilled to ones since their early childhood. This is based on the argument that a good financial attitude and behaviour are not an instant process. The current study tried to gain information about the financial literacy of kindergarten parents, as well as their perceptions and socialization regarding financial literacy education to their children. This study applied a quantitative descriptive study using a questionnaire. Also, a parent meeting was used as a media for collecting data. The findings showed that parents had a fairly good financial literacy as well as good perceptions and socialization of financial literacy education to their children. Although several financial behavior should be improved such as having a budget plan as well as regular savings. For their children, parents also already have good financial habits by providing them with piggy banks and pocket money to be managed. An interesting finding was found that several parents are afraid to talk to their children about money. However, after attending the parent meeting about financial literacy for kids, they know what money management topic should be introduced to kids. Thus, this study is expected to provide a new insight for policymakers in order to design a collaborative and an effective financial education with parents.